Prevalência das infecções por Papilomavírus humano e soropositividade de Chlamydia trachomatis em mulheres portadoras de neoplasias cervicais na região central do Brasil - Guimarães, Narriman Kennia da Silva Barros (2009)
High-risk papillomavirus (HPV) is the etiological agent for cervical neoplasia. However, the presence of singly HPV infection is unlikely to be sufficient for cervical carcinogenesis, and other sexually transmitted infections (STI) may increase the risk of cervical neoplasia. The significance of the association between the human papillomavirus (HPV) and other sexually transmitted infections in the development of cervical neoplasias has been investigated and the more consistent data have pointed to an association with Chlamydia trachomatis (C. trachomatis). However, the exact relationship between C. trachomatis and HPV infection remains not completely understood. It is possible that C. trachomatis infection may be an independent factor or cofactor for HPV in the development of cervical neoplasia. Objective: The objective of this study was to evaluate the seropositivity for Chlamydia trachomatis in HPV-positive women correlating with the severity of cervical neoplasia in central area of Brazil. Methodology: A total of 131 women referred to colposcopic clinic, in Goiás, Brazil because of an abnormal cervical smear were included in the study. HPV DNA was detected by polymerase chain reaction using PGMY09/PGMY11 primers, and genotyping was performed by reverse dot blot hybridization. Seropositivity for C. trachomatis was evaluated using ELISA for the detection of IgG antibodies. Results: The total prevalence of HPV infection was 86.3% (113/131). Seropositivity for C. trachomatis was 26% (34/131). Thirty one women (27.4%; 31/113) tested simultaneously positive for C. trachomatis and HPV. Of these, 12.9% (4/31) tested negative at histology, while 87.1% (27/31) tested positive for CIN and invasive carcinomas. The most prevalent HPV type in the C. trachomatis seropositive women was HPV 16 (51.6%; 16/31) and in these women, this type was present in 50% (2/4) of cases negative, 33.3% (3/9) of cases CIN1, 53.3% (8/15) of cases CIN2/CIN3 and 100% (3/3) of cases invasive carcinoma. Taking as reference cases negative for HPV/ C. trachomatis, the positivity for HPV/ C. trachomatis was significantly associated with CIN 2 or worse diagnostic, especially the types 16 and 18. A borderline significance was observed when the reference was HPV positive and C. trachomatis negative cases. There was a borderline significance between other types of HPV and positivity for C. trachomatis with neoplastic diagnosis considering as reference HPV/ C. trachomatis negative cases. Conclusions: C. trachomatis seropositivity was associated with severity of cervical neoplasia in women HPV positives. Then, it may be important to screen for the simultaneous presence of C. trachomatis which may have synergistic pathological effects.